Resonance: a normative category or figure of uncertainty? On reading Hartmut Rosa with Thomas Mann's The Magic Mountain. Issue 3 (1st September 2020) - Fuchs, Anne
ABSTRACT: This article offers a critical reading of Hartmut Rosa's theory of social resonance in dialogue with Thomas Mann's The Magic Mountain. The article shows that the notion of resonance is meant to correct the inherent determinism which characterized Rosa's earlier work on acceleration. As a responsive mode of being in the world, resonance stands in a dialectical relationship to alienation, redressing the Cartesian split between mind and body. Exploring the inherent tension between resonance as a normative social category and as an aesthetic concept, resonance emerges as a figure of uncertainty which, for good reasons, resists integration into the social world.